Have We Met Before? Pigeons Recognise Familiar Human Faces - Stephan, Claudia; Wilkinson, Anna; Huber, Ludwig (Avian Biology Research, 2012)
Despite growing evidence for the recognition of conspecifics, studies on heterospecific recognition are still scarce. There is some evidence that birds living in urban habitats are able to distinguish between specific humans, depending on their previous experience with them. Nonetheless, the features by which the birds actually discriminated among humans remain unclear. This study investigated whether pigeons are capable of performing such a sophisticated categorisation and the features relevant to making this discrimination. The results revealed that pigeons are able to discriminate reliably between familiar and unfamiliar humans and provide evidence that facial features are important for this recognition. Furthermore, our results suggest that the ability to discriminate between individual heterospecifics is not restricted to bird species that are considered highly cognitive.<br